Simple bone cyst of spinal vertebrae: two case reports and literature review. Issue 11 (30th November 2021) - Safaei, Saeid; Athari, Mirbahador; Azimi, Parisa; Mirbolook, Ahmadreza; Yazdanian, Taravat; Hamzehzadeh, Farhad
Abstract: Simple bone cyst (SBC) is not a common lesion in the spine and especially in the vertebral body. We intend to report two cases of SBC located in the vertebral body, and review the literature. Two cases include a 24 year-old male and 26 year-old male with vertebral body lesion of T12 and L5 vertebrae, retrospectively. Both lesions were found to be SBC and confirmed by pathology. Both cases were managed with surgery, the cavity was filled with bone graft and posterior spinal fusion and instrumentation with pedicle screws, and rods were carried out. There was no recurrence. There have been 21 cases of SBCs in English literature, and only 8 cases have been reported in the vertebral body. SBC is a rare benign lesion in the spine and it should be considered in the differential diagnosis when suggested by radiologic investigations.